Lunar crater names. The invisible face of epistemic violence shining upon us every night - Juszczak, Mark Darius (Pedagogika Społeczna Nova, 2023)
Lunar craters are the only and most significant surface features of a planetary body in Outer Space that are visible to the naked eye. While we can only look at the surface of other planets and their moons through probes, robots and telescopes, the moon requires no instruments or technological tools to be seen. Despite this significant difference – that the Moon’s surface features are visible to any human on a clear night, the history and current process of naming Lunar craters does not recognize that dif- ference. Rather, Lunar craters are subject to the same type of seemingly scientific naming process as that ascribed to the remaining 40 planetary bodies in our Solar System that currently have a naming protocol for surface features. In this paper, I argue that both this lack of distinction and the resistance (under the umbrella of both historical precedent and scientific selenographic naming conventions) to name changes of prominent Lunar craters has resulted in a unique form of post-terrestrial epistemic violence – a violence evident in global social pedagogies of outer space that remain silent on this most important issue of who has the right to name the heavens.